Solubility enhancement mechanism of lovastatin using arginine as co-solute / Nur Farahani Zolkiflee - Zolkiflee, Nur Farahani (2019)
Lovastatin (LVS) is one of the cholesterol lowering drugs categorised as Class II Biopharmaceutics Classification System (BCS). LVS exhibits low aqueous solubility and bioavailability thus presenting a great challenge to formulators. Though various studies have been conducted to enhance its solubility however, very few actually